Aplikasi Sistem Kawalan Pintu Automatik bagi Bangunan Pintar di Malaysia - Saupi, Khairul Firdaus; Omar, Roshartini; Masrom, Md Asrul Nasid; Khalid, Zailawati (Research in Management of Technology and Business, 2025)
Rapid technological advancements have propelled the concept of smart buildings in Malaysia, making the use of automatic door control systems an increasingly essential feature for both employees and users. However, despite the convenience and accessibility offered by these systems, cybersecurity has emerged as a critical aspect that cannot be overlooked. Cybersecurity threats in Malaysia have escalated over the past few years, particularly in terms of frequency and severity of attacks. Therefore, the objective of this study is to identify the key challenges faced, examine the impacts of the application of automatic door control systems on cybersecurity and user privacy in smart buildings, and propose suitable strategies to enhance cybersecurity and privacy when using automatic door control system applications in smart buildings in Kuala Lumpur, Malaysia. The respondents of this study comprise employees and users involved in smart buildings utilizing automatic door control system applications. This research employs a quantitative method for data collection, utilizing Google Forms questionnaires distributed to respondents. The study population consists of 364 individuals, with a response rate of 98.35%, resulting in 358 valid responses. Data were analyzed descriptively using the Statistical Package for the Social Science (SPSS) software, version 27. The findings indicate that continuous maintenance support is the primary challenge faced, while operational disruptions emerge as the main impact highlighted in this study. Furthermore, the implementation of enhanced firewalls designed to filter incoming and outgoing access is identified as the most effective strategy for improving cybersecurity and privacy when using automatic door control system applications in smart buildings in Malaysia. The significance of this study lies in its relevance to users of automatic door control system applications, providing comfort and enhancing the security of their environments.